2013
DOI: 10.1177/0892705713486136
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the processing parameters of polymer conductive semicrystalline polymer composites with carbon black

Abstract: This work presents how the optimization of polymer conductive composites constituting the semi-crystalline polymer matrix (low-density polyethylene (LDPE) and isotactic polypropylene (it-PP)) and carbon black (CB) by melt-mixing process, has an important influence not only in diminishing the resistivity of the composite but also in reducing the critical concentration of CB. The experimental procedure consists of studying the influence of processing parameters such as mixing temperature, time, and speed on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The resistance increase during return was determined due to the hybrid composite’s low filler content 35,36 (7 phr CB and 1 phr GE termed HNGE01) due to the excess rubber matrix. Even when the strain values for this material (HNGE01) went up to 5%, sometimes remarkably high resistance measurements were taken, and the material showed an insulator character.…”
Section: Resultsmentioning
confidence: 99%
“…The resistance increase during return was determined due to the hybrid composite’s low filler content 35,36 (7 phr CB and 1 phr GE termed HNGE01) due to the excess rubber matrix. Even when the strain values for this material (HNGE01) went up to 5%, sometimes remarkably high resistance measurements were taken, and the material showed an insulator character.…”
Section: Resultsmentioning
confidence: 99%
“…They reported that it was possible to prepare a conductive material with a lower concentration of conductive particles (the critical concentration was calculated as 13.7 wt.% CB for LDPE and 4.9 wt.% CB for it-PP) by improving the processing conditions for composites. 21 Oil additives have long been utilized as a processing aid in the polymer sector due to their several benefits. They improve the dimensional stability of extruded materials, reduces molding filling time and curing cycle time, improves the ozone resistance of the rubber compound, minimizes plasticizer migration to the surface of rubber component, and have capability to regulate flow under mechanical pressure.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that it was possible to prepare a conductive material with a lower concentration of conductive particles (the critical concentration was calculated as 13.7 wt.% CB for LDPE and 4.9 wt.% CB for it-PP) by improving the processing conditions for composites. 21…”
Section: Introductionmentioning
confidence: 99%
“…Most of the polymer composites are produced in liquid phase, in a melt stage, or in monomer or polymer dissolution. In both cases, a suspension is always formed and it has been studied that the resistivity control for melt polymer composites is also dependent on processing parameters such as mixing time, temperature, rotor speed, molding time, temperature, and pressure at molding [43][44][45][46][47][48][49]. For a composite obtained by in situ method that consists in making first a dispersion of carbon particles into the monomer and then a subsequent polymerization of that suspension, the optimization of the processing parameters is more difficult.…”
Section: Introductionmentioning
confidence: 99%